Suspension of Esophageal Stent: An Endoscopic Technique for the Treatment of Esophagopleural Fistula - , Chunsi Zheng, Chunsi Zheng, Jingbo Yang (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Zheng C, Yang J. Suspension of esophageal stent: An endoscopic technique for the treatment of esophagopleural fistula. Turk J Gastroenterol. 2024;35(5):418-420.